To pass or not to pass: A qualitative inquiry on students’ views on the academic retention policy - Mark Lloyd E. Oding; Jemarie A. Palang-at; Ariel E San Jose (Journal of Education and Learning (EduLearn), 2021)
Retention policy is an important guiding principle implemented by academic institution to promote students’ development, yet evidence is unable to disentangle how the eﬀect of retention policy varies by the outcome in student’s intellect and morality. This study gathered the views and perspectives of students in relation to the retention policy of the college. This study used the qualitative-phenomenological method. Seven participants who gained the lowest general percentage average were purposively selected. In-depth interviews were conducted to obtain the pertinent information. Results revealed that retention policy was a source of encouragement for students to perform well and it was a necessity to develop and enhance students’ cognition. However, few students mentioned that the retention policy was a source of stress because they needed to comply with the standard requirements imposed by the college. They reiterated that the policy discriminated against slow-learners. The findings implicate that concrete actions may be done to address the misconception on the retention policy. Strong academic support and resources may be offered to address students’ needs especially to those who were at-risk. Retention policy will remain a challenge to all students if the academic institution is not fully equipped to respond to the needs of the students.